1984
DOI: 10.3758/bf03198313
|View full text |Cite
|
Sign up to set email alerts
|

Using both an auditory and a visual short-term store to increase digit span

Abstract: Can digit span be increased by storing digits nonredundantly in both an auditory short-term store and a visual short-term store (dual storage)? In Experiment 1, when four digits were presented visually and then the remaining digits were presented auditorily, digit span increased three digits over a baseline measurement, but only when the auditorily presented digits were reported first (inverted response). Normal order of response for this presentation was not as effective. Possible reasons for the advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…Using a sequential presentation, no large increases in recall have been found (Murdock & Carey, 1972;Murdock & Walker, 1969); the small increases that are found could be attributed to the fact that presenting stimuli in two modalities groups the stimuli, which improves recall (Ryan, 1969). Using a simultaneous presentation, recall can be increased (Frick, 1984). In a pilot experimentto that study, I tested both sequential and simultaneous visual presentations (of the to-be-remembered visual stimuli).…”
Section: Previous Researchmentioning
confidence: 93%
“…Using a sequential presentation, no large increases in recall have been found (Murdock & Carey, 1972;Murdock & Walker, 1969); the small increases that are found could be attributed to the fact that presenting stimuli in two modalities groups the stimuli, which improves recall (Ryan, 1969). Using a simultaneous presentation, recall can be increased (Frick, 1984). In a pilot experimentto that study, I tested both sequential and simultaneous visual presentations (of the to-be-remembered visual stimuli).…”
Section: Previous Researchmentioning
confidence: 93%
“…In an extensive review, Penney (1989) considered research in which the presentation material was a mixture of the auditory and visual modalities and suggested that the effective capacity of working memory can be increased by using both visual and auditory channels. One of the most cited examples of modality effects in the literature is the superior recall for lists of items when they are presented in visual and auditory modalities rather than just in one modality (Frick, 1984). Many studies also show that attention can be better divided between the eye and ear than between two auditory or two visual channels (Wickens, 1984).…”
Section: Modality Principlementioning
confidence: 99%
“…For example, Frick (1984) found that if people were presented visually with a set of items followed by a series of auditory items, recall was better than it was if both sets of items were presented in either the auditory or the visual mode. (The dual mode result was obtained only if participants were required to report the auditory items first.)…”
Section: Modality Effectsmentioning
confidence: 99%